Mutations in TSPAN12 Cause Autosomal-Dominant Familial Exudative Vitreoretinopathy - Poulter, James A. (Elsevier, 2010)
Familial exudative vitreoretinopathy (FEVR) is an inherited blinding disorder of the retinal vascular system. Although mutations in three genes (LRP5, FZD4, and NDP) are known to cause FEVR, these account for only a fraction of FEVR cases. The proteins encoded by these FEVR genes form part of a signaling complex that activates the Norrin-β-catenin signaling pathway. Recently, through a large-scale reverse genetic screen in mice, Junge and colleagues identified an additional member of this signaling complex, Tspan12. Here, we report that mutations in TSPAN12 also cause autosomal-dominant FEVR. We describe seven mutations identified in a cohort of 70 FEVR patients in whom we had already excluded the known FEVR genes. This study provides further evidence for the importance of the Norrin-β-catenin signaling pathway in the development of the retinal vasculature and also indicates that more FEVR genes remain to be identified.